ANALISIS PENGARUH EVA, EPS DAN BEP TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEITAHUN 2012 - Ibnu Ruslan Mughni, (2013)
This study was conducted to examine the effect of variable Economic Value Added (EVA), Earning Per Share (EPS), and Basic Earning Power (BEP) of the Stock Price on companies listed on the Indonesia Stock Exchange in 2012. The population number of 140 manufacturing companies listed on the Indonesia Stock Exchange in 2012. Data obtained from the published financial statements of the company. Obtained a total sample of 50 firms in this study. The analysis technique used is multiple linear regression and t-test using statistical hipotetsis and F-statistics with a confidence level of 5%. These results indicate that the Economic Value Added (EVA), Earning Per Share (EPS), and Basic Earning Power (BEP) significant effect on stock price. We suggest to investors in the Indonesia Stock Exchange in order to pay attention to other factors that affect stock price in making an investment decision. Variables Basic Earning Power (BEP) in this study is the most influential variable on Stock Price indicated from the constant value of 0.391, which means if the stock price goes up 1 then the value of BEP will increase by 0.391.